The Anatomy of a failed industrial policy developing aluminium industry in Trinidad and Tobago - Barclay, Lou Anne (2012)
Posits that the institutional framework for implementing industrial policy in today's economic and political context needs to have the characteristics of embedded autonomy, but at the same time it needs to address the issues of accountability and transparency.